A H2O2-free electrochemical peptide biosensor based on Au@Pt bimetallic nanorods for highly sensitive sensing of matrix metalloproteinase 2. Issue 45 (11th May 2020) - Xi, Xiaoxue; Wen, Meiqi; Song, Shihao; Zhu, Junlun; Wen, Wei; Zhang, Xiuhua; Wang, Shengfu
Abstract : We construct for the first time a H2 O2 -free electrochemical peptide biosensor based on Au@Pt bimetallic nanorods in neutral substrate solutions for highly sensitive detection of matrix metalloproteinase 2. Abstract : Inspired by the excellent catalytic activity of Au@Pt bimetallic nanorods, we construct a H2 O2 -free electrochemical peptide biosensor based on Au@Pt bimetallic nanorods for highly efficient and sensitive sensing of MMP-2 for the first time, not only simplifying the traditional testing steps but also avoiding the potential damage caused by H2 O2 to peptides and proteins.